2013
DOI: 10.1007/s10495-013-0878-7
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stromal/stem cells assist fat transplantation reducing necrosis and increasing graft performance

Abstract: Autologous fat transfer (AFT) is a procedure for adipose tissue (AT) repair after trauma, burns, post-tumor resections and lipodystrophies still negatively impacted by the lack of graft persistence. The reasons behind this poor outcome are unclear and seem to involve damages in either harvested/transplanted mature adipocytes or on their mesenchymal progenitors, namely adipose stromal/stem cells (ASC), and due to post-transplant AT apoptosis and involution. A rabbit subcutaneous AT regeneration model was here d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 49 publications
(77 reference statements)
6
52
1
1
Order By: Relevance
“…The following factors influence the long-term retention of fat grafts. First, it depends on the extent of cell injury or death caused by surgeryinduced injury at the early stage of transplantation before the new blood supply of the graft is established [10,25]. Using Perilipin A immunofluorescence staining and the TUNEL assay, this study demonstrated that syngeneic ASCs can alleviate injury and reduce apoptosis, which is consistent with findings of other investigators [10,26].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The following factors influence the long-term retention of fat grafts. First, it depends on the extent of cell injury or death caused by surgeryinduced injury at the early stage of transplantation before the new blood supply of the graft is established [10,25]. Using Perilipin A immunofluorescence staining and the TUNEL assay, this study demonstrated that syngeneic ASCs can alleviate injury and reduce apoptosis, which is consistent with findings of other investigators [10,26].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the longterm retention of fat grafts was our first concern in this study. Graft volume continues to decline until 3 months post-transplantation [22], and therefore the third month post-transplantation was regarded as the most appropriate time point to measure the long-term volume retention of fat grafts in small animal models, which are consistent with previous studies [10,23,24]. The following factors influence the long-term retention of fat grafts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This immunosuppression of T lymphocytes was also demonstrated to reduce the severity of symptoms in rheumatoid arthritis [60]. ASCs were also shown to decrease the incidence of necrosis following autologous fat grafting [114]. Through the upregulation of VEGF and IL-10, intracerebral implantation of ASCs demonstrated significantly improved functional outcomes in a mouse model of Alzheimer's disease [115].…”
Section: Immunomodulation In Transplantation and Immune-mediated Diseasementioning
confidence: 95%